“La psicomotricidad fina en el proceso de aprendizaje de los niños de Educacion Inicial” - Changoluisa Clavijo, Taña Maribel (2023)
The present investigation with the theme "Fine psychomotor skills in the learning process of children in initial education", aims to diagnose fine psychomotor skills in the learning process through playful techniques for the improvement of the digital clamp in children of initial education of the different Educational Institutions of the rural Angamarca Parish, in this investigation the interpretive paradigm was used with the qualitative approach that is mainly oriented on the knowledge, opinions and attitudes of the participants who are involved within the field of study using the method inductive and field, which seeks to contribute with new elements to develop psychomotor skills in the learning process of infants, it is worth mentioning that the in-depth interview technique and direct observation were applied to retrieve information, where it was possible to conclude that the Children do not have good fine motor skills, since teachers are not trained and specialized to work with Initial infants.